Development of Digital Pop-up Book Media to Increase Interest and Learning Outcomes on Water Cycle Material - Azzahrani, Kamila; Sukasih, Sri (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Science, which studies living beings and inanimate objects in the universe, requires engaging learning media to foster students’ interest in learning. A problem was identified at SDN Ngaliyan 05, where the lack of varied learning media and the monotonous use of textbooks resulted in low interest and incomplete learning achievement related to the water cycle material, as per KKTP standards. This study aims to develop, analyze the validity, and assess the effectiveness of digital Pop-up Book media to enhance interest and learning outcomes in the water cycle material for fifth-grade students. The research method used is research and Development (R&D) with the ADDIE model. The results show that digital Pop-up Book media is highly feasible, with validation scores of 87.5% from material experts, 97.5% from media experts, and 97.5% from practitioners. The media effectively increases interest and learning results as determined by t-test analysis, with a sig. (2-tailed) value of 0.000 < 0.05. The N-gain test result shows a moderate improvement in learning interest 0.63 and learning outcomes 0.67. In conclusion, the digital Pop-up book media enhances interest and learning outcomes in the water cycle material.